H2S-activatable near-infrared afterglow luminescent probes for sensitive molecular imaging in vivo - Luyan Wu (Nature Portfolio, 2020)
Afterglow imaging probes are of interest for in vivo imaging due to high signal-to-background ratios. Here, the authors report on an afterglow nanoparticle which is activated by hydrogen sulphide and demonstrate the measurement of hydrogen sulphide levels and the labelling of hepatic cancer specimens in vivo.